Radiographic Assessment of Soft Palate Variations in OSMF Patients - Punia, Himanshu; N, Anup (Journal of Neonatal Surgery, 2025)
Background: Oral Submucous Fibrosis (OSMF) is a chronic, progressive disorder characterized by fibrosis of the oral mucosa, leading to functional impairments. The soft palate, an essential structure in phonation, deglutition, and respiration, undergoes morphological changes in OSMF patients. This study aimed to assess soft palate variations in OSMF using lateral cephalometry. Materials & Methods: A cross-sectional radiographic study was conducted on 200 clinically diagnosed OSMF patients. Lateral cephalometric radiographs were obtained and analyzed for soft palate morphology based on You M et al.'s classification. Statistical analyses were performed using SPSS software, with a significance level set at p<0.05. Results: The study revealed significant morphological variations in the soft palate among OSMF patients. Leaf-shaped morphology was predominant in controls (64%) but decreased in OSMF patients (44%), with an increase in Butt-shaped (22%) and Crook-shaped (12%) palates (p<0.001). Velum length was significantly reduced in OSMF patients (28.38 ± 2.98 mm) compared to controls (37.28 ± 4.52 mm) (p<0.001), while velum width was significantly larger (p<0.001). Disease severity correlated with progressive morphological alterations, with more severe OSMF stages exhibiting higher proportions of Butt and Crook shapes. Conclusion: Lateral cephalometry effectively identifies soft palate morphological changes in OSMF patients, aiding in early diagnosis and disease staging. The progressive shortening and distortion of the soft palate highlight its diagnostic relevance in assessing fibrosis severity. Radiographic evaluation can serve as a valuable tool for clinicians in managing OSMF and preventing severe functional impairments.